Biotransformation of 5-hydroxy-methylfurfural into 2, 5-furan-dicarboxylic acid by bacterial isolate using thermal acid algal hydrolysate. (August 2016) - Yang, Chu-Fang; Huang, Ci-Ruei
Highlights: Optimum thermal acid hydrolysis condition of Chaetomorpha linum was established. Strain Burkholderia cepacia H-2 biotransforming 5-HMF into FDCA was isolated. 5-HMF concentration and pH value deeply influenced FDCA production. 5-HMF biotransformation in the acid algal hydrolysate was performed. 5-HMF detoxification and FDCA production in the algal hydrolysate was feasible. Abstract: Thermal acid hydrolysis is often used to deal with lignocellulosic biomasses, but 5-hydroxy-methylfurfural (5-HMF) formed during hydrolysis deeply influences downstream fermentation. 2, 5-Furan-dicarboxylic acid (FDCA), which is in the list of future important biomass platform molecules can be obtained using 5-HMF biotransformation. Based on the connection between 5-HMF removal in acid hydrolysate and FDCA production, the optimum thermal acid hydrolysis condition for macroalgae Chaetomorpha linum was established. Potential microbes capable of transforming 5-HMF into FDCA were isolated and characterized under various parameters and inoculated into algal hydrolysate to perform 5-HMF biotransformation. The optimum hydrolysis condition was to apply 0.5 M HCl to treat 3% algal biomass under 121 °C for 15 min. Isolated Burkholderia cepacia H-2 could transform 2000 mg/L 5-HMF at the initial pH of 7 at 28 °C and 1276 mg/L FDCA was received. Strain B . cepacia H-2 was suitable for treating the algal hydrolysate without dilution, receiving 989.5 mg/L FDCA.